Linking Services to Manufacturing Exports - Björn Thor Arnarson; Joakim Gullstrand (Lund University, School of Economics and Management, Department of Economics, 2017)
In this paper we analyse the interplay between services and manufacturing. This is done through identifying and quantifying a direct link between manufacturing exports and the sales by service providers. For identification of this transmittance mechanism, with the help of highly detailed geographic data, we create a Localised Export Exposure (LEE) variable that captures the variation in demand for service inputs based on nearby exporters. Since service firms are much less geographically specialised than manufacturing firms, we observe a high variation in their exposure to demand changes. This spatial variation in the demand for service inputs results from a variation in local export volumes (LEE); which is used to assess the interplay between manufacturing exports and services. Our results show that a 1% increase in exports increases the volume of sales of service firms by 0.2% (and employment within the firm by 0.06%). The results show also that the link is highly local and the strongest impact is within 20 km of the shock.
Keywords: F10; F14; F60; 330; Spillovers; Services; Manufacturing Exports; Input-output linkages